2012
DOI: 10.4161/mge.20265
|View full text |Cite
|
Sign up to set email alerts
|

Can silencing of transposons contribute to variation in effector gene expression inPhytophthora infestans?

Abstract: Transposable elements are ubiquitous residents in eukaryotic genomes. Often considered to be genomic parasites, they can lead to dramatic changes in genome organization, gene expression, and gene evolution. The oomycete plant pathogen Phytophthora infestans has evolved a genome organization where core biology genes are predominantly located in genome regions that have relatively few resident transposons. In contrast, disease effector-encoding genes are most frequently located in rapidly evolving genomic region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 39 publications
0
30
0
Order By: Relevance
“…Silencing observed in this study resulted in the development of resistant lines, this may be due to expression of the target gene being dependent upon, or controlled by, transposon elements associated with the effectors (Whisson et al 2012). Silencing leads to a near complete loss of target transcript, though partial silencing may also be observed due to the cumulative effect of PTGS and TGS (Ah Fong et al 2008).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Silencing observed in this study resulted in the development of resistant lines, this may be due to expression of the target gene being dependent upon, or controlled by, transposon elements associated with the effectors (Whisson et al 2012). Silencing leads to a near complete loss of target transcript, though partial silencing may also be observed due to the cumulative effect of PTGS and TGS (Ah Fong et al 2008).…”
Section: Discussionmentioning
confidence: 91%
“…Partial silencing of the potato cultivars can be explained thus, although expression of target gene mRNA is reduced, a small amount of transcript remains, and this is sufficient to maintain wild-type functionality. Whisson et al (2012) suggested RXLR effector genes are preferentially located in genomic regions heavily populated with transposons, and small RNAs involved in silencing can extend from the genome region spanning the effector and transposons. In the future, we plan to further mine the siRNA inhibitor and stacking of other effector genes on single or multiple constructs, and to study the influence of nearby transposons on the evolution and expression of effectors that provide high levels and durable resistance against late blight disease.…”
Section: Discussionmentioning
confidence: 99%
“…Further, a gene-TE transcriptional fusion can lead to the silencing of the introduced fusion construct in P. infestans , as well as the endogenous copies of the gene and TE 11 . Approximately half of the predicted 563 RxLR effectors in P. infestans are located within 2 kb of a transposon sequence, including the PiAvr2 , PiAvrBlb2 , PiAvrBlb1 , and PiAvr4 effector genes encoding avirulence proteins recognized by potato R -genes 17 . Mapping of sRNAs to RxLR effector genes, neighboring TEs, and the intervening sequences (up to 2 kb) revealed evidence for sRNAs derived from both sequences, and included sRNAs that mapped into the interval between both sequences, suggestive of silencing across the entire genomic region.…”
Section: Do Tes and Silencing Lead To Diversification Of Pathogenicitmentioning
confidence: 99%
“…In middle and bottom models, gene position on the P. infestans genome sequence is shown below the gene model; vertical black bars indicate the abundance of aligning sRNAs. More detailed proposed models for sRNA biogenesis and silencing in Phytophthora can be found elsewhere 17 , 29 …”
Section: Do Tes and Silencing Lead To Diversification Of Pathogenicitmentioning
confidence: 99%
“…RXLR and CRN effectors are specifically induced during the infection process. Interestingly, siRNAs were found to co-regulate retrotransposons and the surrounding CRN effectors [57,58], which impacts the interaction between the host and the pathogen [59]. How the production of effector gene-related siRNAs is regulated is currently unclear.…”
Section: Introductionmentioning
confidence: 99%